Pedagogy of the arts for building healthy habits in Colombian children and adolescents with obesity or prediabetes (2021)
Understand and experience the corporeity in Colombian children and adolescents with obesity or pre-diabetes through artistic practices as a possibility of reflective and observable action in the incorporation of healthy bodily habits.